2016
DOI: 10.1093/ckj/sfw055
|View full text |Cite
|
Sign up to set email alerts
|

The risk of acute kidney injury following transapical versus transfemoral transcatheter aortic valve replacement: a systematic review and meta-analysis

Abstract: BackgroundThe aim of this systematic review is to examine the literature for the risk of acute kidney injury (AKI) in patients who underwent transcatheter aortic valve replacement (TAVR) based on transapical (TA) versus transfemoral (TF) approaches.MethodsA literature search was conducted utilizing Embase, Medline, Cochrane Database of Systematic Reviews and ClinicalTrials.gov from inception through December 2015. Studies that reported relative risk, odds ratio or hazard ratio comparing the AKI risk in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
3
24
1
Order By: Relevance
“…Diabetes mellitus, prior PCI, use of IABP, and need for blood transfusion were independently associated pAKI risk factors. While the transapical approach has been shown to increase TAVR‐related AKI when compared with the transfemoral approach, it has not been correlated with severe or long‐term renal dysfunction . We did not find any association between the different TAVR approaches with pAKI or its outcomes.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Diabetes mellitus, prior PCI, use of IABP, and need for blood transfusion were independently associated pAKI risk factors. While the transapical approach has been shown to increase TAVR‐related AKI when compared with the transfemoral approach, it has not been correlated with severe or long‐term renal dysfunction . We did not find any association between the different TAVR approaches with pAKI or its outcomes.…”
Section: Discussioncontrasting
confidence: 63%
“…Previous studies, including a very recent study by Aalaei‐Andabili et al, have identified important predictive factors for AKI after TAVR, including pre‐existing chronic kidney disease, diabetes mellitus, use of the transapical approach, need for circulatory support, peripheral artery disease, prior coronary artery bypass grafting, and periprocedural blood transfusion, suggesting close surveillance for AKI especially within 7 days after TAVR in these high‐risk populations . In the present study, we investigated potential risk factors for pAKI after TAVR.…”
Section: Discussionmentioning
confidence: 81%
“…1,2,4 Previous studies have attempted to identify novel biomarkers of AKI to allow earlier intervention and develop more effective pharmacological treatments and strategies. 1,3,[5][6][7][8][9] However, these have been mostly unsuccessful. 7,10 Hence, identifying high-risk patients for developing AKI is critical in order to prevent AKI events.…”
Section: Introductionmentioning
confidence: 99%
“…Transcatheter aortic valve replacement (TAVR) has globally expanded in the past decade and now is acknowledged as a standard approach for patients who have severe aortic stenosis (AS) deemed inoperable with high surgical risk for open-heart aortic valve replacement surgery (1)(2)(3)(4)(5)(6). In addition, the recently published studies also suggest that patient selection for TAVR is evolving toward treating lower surgical risk patients (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%